The Correlation Between Type of Land Use and Water Quality in the Rembangan River, Jember Regency - Wardiani, Fefi Eka; Wimbaningrum, Retno; Setiawan, Rendy (Jurnal ILMU DASAR, 2019)
The river is one of the important water sources and at this time the river water quality has decreased.The type of land use around the river is thought to have a significant contribution to river water quality. This research was conducted to determine of correlation between the type of land use and water quality in Rembangan River, Jember Regency.The study was carried out at four stations that passed through secondary forests, coffee plantations, rice fields and residential housing. The data of biodiversity and density of plants and physical-chemical parameters of river water were noted, and benthic macroinvertebratessamples were collected at each station. Data of biodiversity and density plants were used to determine of environmental services index (ESI) values. Benthic macroinvertebrates samples were identifiedat the family level, and after that the tolerance score and the abundance of each family was determined. The last two data were analyzed to determine of Family Biotic Index (FBI) values.The value of ESI, physico-chemical parameters of river waterand FBI were analyzedto determine the relationship between these variables by using Pearson correlation analysis (α < 0.05).The research result revealed that the type of land use (ESI) was significantly related to the biological quality of river water (FBI) as indicated by the p value > 0.05. The correlation characteristic is negative and very strong (R = 0.886). High ESI values indicate that the diversity and carbon sequestration of plant community around the river are in good condition and vice versa. Low HBI values indicate good river water quality and vice versa. Based on this research, each land use type must provide space for the natural growth of the plant communityto maintain the quality of river water to remain good. Keywords: river, benthic macroinvertebrates, land use, water quality, ESI, HBI.